1992
DOI: 10.1139/v92-307
|View full text |Cite
|
Sign up to set email alerts
|

Boron-11, boron-10, and nitrogen-14 NMR relaxation rates and quadrupole coupling constants in BH3NH3

Abstract: . Can. J. Chem. 70, 2420 (1 992). The "B, "B, and I4N spin-lattice relaxation times (TI) for aqueous solutions of BH,NH, were measured by NMR spectroscopy. The results of this investigation are consistent with the nuclear quadrupolar coupling constants reported in previous nuclear quadrupolar resonance and microwave studies. The activation energy associated with rotational reorientation of BH3NH3 in aqueous solution is 1 1.7 * 0.6 kJ/mol. Electric field gradients were calculated at various levels of ab initio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although the x values are not quantitatively reproduced, the trend of decreasing x with decreasing size of the E-atom is apparant. It has been shown that x values calculated with large basis sets (e.g., 6-3 lG*) and at levels where second-order correlation effects are taken into account (e.g., MP2 or CI) are in good aggreement with those obtained from gas phase experiments (e.g., microwave spectroscopy) (25)(26)(27). The large size of the S e and T e atoms has restricted our calculations to the STO-3G* basis; therefore electron correlation effects are not taken into account.…”
Section: Variation Of Y In the Series (Ch)e+mentioning
confidence: 93%
“…Although the x values are not quantitatively reproduced, the trend of decreasing x with decreasing size of the E-atom is apparant. It has been shown that x values calculated with large basis sets (e.g., 6-3 lG*) and at levels where second-order correlation effects are taken into account (e.g., MP2 or CI) are in good aggreement with those obtained from gas phase experiments (e.g., microwave spectroscopy) (25)(26)(27). The large size of the S e and T e atoms has restricted our calculations to the STO-3G* basis; therefore electron correlation effects are not taken into account.…”
Section: Variation Of Y In the Series (Ch)e+mentioning
confidence: 93%
“…Figure 6. Temperature dependence of the boron NMR spectra of (9) in the presence of pyridine-d5 (0.5 eqv.) acquired by using 11 B single pulse (left), 11 B-DEPTH (middle) and 10…”
Section: Bmentioning
confidence: 99%
“…Indeed, 10 B NMR applications are limited to special cases, e.g. measurement of J ‐couplings, mechanistic investigations based on 10 B labelling, relaxation studies, boron neutron capture therapy of cancer and the solid‐state NMR of boron doped diamond.…”
Section: Introductionmentioning
confidence: 99%
“…In solution, the dipole moment has been measured and the vibrational modes have been assigned . The 11 B, 14 N, 15 N, and 1 H chemical shifts and spin−spin coupling constants have been measured in a number of solvents. The 11 B, 10 B, and 14 N spin−lattice relaxation times ( T 1 ) have been measured in aqueous solution and related to the nuclear QCCs as obtained by microwave spectroscopy, nuclear quadrupolar resonance (NQR) spectroscopy, and ab initio molecular orbital theory …”
Section: Introductionmentioning
confidence: 99%